The Level of Smash Skills on Male Athletes of BVC Volleyball Club - Putra Wahyu Nur Septiawan; Norma Anggara; Mita Erliana (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
This study aims to obtain data as a basis for evaluating and improving smash technique training of male athletes at the BVC Club in Balangan District to serve as a reference in designing a more focused and athlete-needs-based training program. The method used is quantitative method with total sampling technique on 12 male athletes. The data collection instrument consists of a smash skill test based on the reference by Tantri & Mashud (2023). The results of the study indicate that 41.66% of athletes (5 individuals) are in the very good category, 16.67% (2 individuals) in the good category, 16.67% (2 individuals) in the medium category, and 25% (3 individuals) in the poor category, with no athletes in the very poor category. These findings suggest that some athletes have mastered smash technique well, but there are still a significant number of athletes who require special attention in mastering the technique, particularly in terms of power, attack angle, and shot accuracy. This study recommends the need for regular evaluations and the development of more structured and individually tailored technical training programs to improve overall smash performance.